Analisis Kenaikan Tarif PPN dan Cukai Terhadap Penerapan Pajak Pertambahan Nilai (PPN) pada PT.Panen Boyolali - Lia Nur Hidayani; LMS Kristiyanti; Sri Laksmi Pardanawati (Jurnal Akuntansi dan Pajak, 2024)
This research aims to find out how to analyze the application of Value Added Tax at PT. Panen Boyolali and how to analyze the impact of increasing VAT and Excise rates on the implementation of Value Added Tax at PT. Panen Boyolali. This research uses descriptive research with a quantitative approach. The results of this research indicate that PT. Panen Boyolali in calculating, depositing and reporting Value Added Tax is in accordance with applicable laws. Then the results of the analysis of the impact of increasing VAT and Excise rates on the application of Value Added Tax at PT. Panen Boyolali has an impact on the Company's sales.